Comparative Study of Root Coverage Using Semilunar Coronally Repositioned Flap with and without Topical Application of Tetracycline Solution - H Golestaneh; S Amini (Isfahan University of Medical Sciences, 2006)
•Introduction: Treatment of gingival recession has been one of the most important aims of periodontalprocedures and therefore introduction of a predictable technique for covering the denuded roots hasbeen an ideal goal for many years.The purpose of this study was the evaluation of root coverage by ";Semilunar coronally repositionedflap"; technique; and the role of topical application of tetracycline hydrochloride in improvement of theresults.•Methods and Materials: 24 anterior and premolar teeth were selected from 9 patients and dividedrandomly in two ";test and control"; groups. After completion of initial procedure and before operation,some quantitative (Vertical recession, depth of gingival sulcus and width of keratinized gingiva), andqualitative variables (Sensitivity of root surface to air flow and feeling of an unsatisfactory appearanceby the patient oneself) were measured.In test group, tetracycline 1% (pH = 2.3) was applied 3 minutes by burnishing method on the surfaceof root, before performance of surgery.The patients were visited at the days 7, 14, 30, and 90 after the operation, and healing of the area andhygiene status were evaluated.•Results: Following statistical analysis, it was concluded that recession depth has been reducedsignificantly in both groups, 1 and 3 months after the operation.• The mean root coverage in test group was 2.29 mm (70.33% coverage), and 2.16 mm (67.33%coverage), 1 and 3 months after surgery, respectively.• Width of keratinized tissue was also increased significantly in both groups.• Among the quantitative variables, only probing depth did not alter during the period of research.• Qualitative variables were also improved significantly in both groups.• Apparently, the application of solution as a ";root conditioning agent"; did not influence the results ofthis study.•Conclusion: In summary, the operation technique may be an appropriate procedure for the coverageof the anterior teeth in maxilla, based on its unique advantages.•Key words: Gingival recession, Root coverage, Semilunar coronally repositioned flap, Topical tetracycline,Root sensitivity, Keratinized gingiva